(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
This scientific research paper aims to study the French forest policy towards the fires witnessed in the department of Constantine. specifically the two mixed municipalities Sefia and Souk Ahras of the arroundissement of Guelma, which experienced a series of serious fires in 1890 that left heavy losses in the forest cover of this region and severe damage suffered by pastoral forest tribes. This was done through analyzing the archival documents found in box GGA, 86.108, which contained an important collection of reports of the French gendarmerie teams (gendarmerie), as well as the correspondence of the forest guards (les gardes champétres). Which proved that the French forest exploitation was extensive. That is by expropriating large forest properties from the Algerian population after the French administration accused them and held them responsible for the fires in most cases.